VARIABILITY IN THE CHEMICAL AND MINERALOGICAL CHARACTERISTICS IN SOILS FROM CURITIBA METROPOLITAN AREA (PR) - BARBAR, Leila Chamma; MELO, Vander de Freitas (Scientia Agraria, 2008)
Aiming to evaluate the variations in the total elements contents and mineralogical characteristics in a short horizontal soil distance, four composite samples (repetitions) were taken from A and B horizons in five areas in the Curitiba Metropolitan Region. The silt+clay fraction was investigated by X-ray diffraction, differential thermal analysis, thermogravimetry and chemical analysis. Total Si, Al and Fe contents were determined after clay sample digestion by concentrated acids (HF, HNO3, H2SO4 e HClO4). The Fe and Al contents were determined from ammonium oxalate (AO), citrate-bicarbonate-dithionite (CBD) and NaOH 0,5 mol L-1 extracts. It was observed variations in the mineralogical characteristics between replications in the same area, mainly for soils originated from limestone and claystone rocks. The variation coefficient (VC) was inversely related to stability of the characteristics analyzed: total element contents and crystalline mineral contents had lower VC values; opposite behavior was observed to Fe and Al amorphous oxide contents. The crystallography characteristics of the kaolinite and gibbisite were relatively homogeneous.